MEASUREMENT OF THE RULE OF LAW’S PERCEPTION FROM THE PERSPECTIVE OF PUBLIC ADMINISTRATION IN TURKEY (Third Sector Social Economic Review, 2019)
The desire to approach the ideal of the rule of law can vary from society to society, from actor to actor. Because at certain times and space, the political aim that the actors who give meaning to the state of law wants to achieve may not meet the expectations of other stakeholders. On the other hand, it is also a controversial issue just any institution claimed to be internationally accepted to decide Republic of Turkey’s rule of law ideal how close or not. The first aim of this study is to determine why the rule of law is necessary for Turkish Public Administration. The second is to contribute to the Turkish Public Administration literature by deriving concrete criteria about how the measurement should be made. Content analysis method was used in the study. According to the findings obtained from the reports, documents and sources in the literature, 8 main criteria and a total of 51 sub-criteria were derived and proposed in the conclusion section. In addition, a questionnaire was developed based on these criteria.
Keywords: Turkey; Public Administration; State of Law; The Rule of Law; Measuring the State of Law